Biological functions of sialic acid as a component of bacterial endotoxin - Dudek, Bartłomiej; Rybka, Jacek; Bugla-Płoskońska, Gabriela; Korzeniowska-Kowal, Agnieszka; Futoma-Kołoch, Bożena; Pawlak, Aleksandra; Gamian, Andrzej (Frontiers in Microbiology, 2022)
Lipopolysaccharide (endotoxin, LPS) is an important Gram-negative bacteria antigen. LPS of some bacteria contains sialic acid (Neu5Ac) as a component of O-antigen (O-Ag), in this review we present an overview of bacteria in which the presence of Neu5Ac has been confirmed in their outer envelope and the possible ways that bacteria can acquire Neu5Ac. We explain the role of Neu5Ac in bacterial pathogenesis, and also involvement of Neu5Ac in bacterial evading the host innate immunity response and molecular mimicry phenomenon. We also highlight the role of sialic acid in the mechanism of bacterial resistance to action of serum complement. Despite a number of studies on involvement of Neu5Ac in bacterial pathogenesis many aspects of this phenomenon are still not understood.